Expanding Tara Oceans Protocols for Underway, Ecosystemic Sampling of the Ocean-Atmosphere Interface During Tara Pacific Expedition (2016–2018) - Gorsky, Gabriel; Bourdin, Guillaume; Lombard, Fabien; Pedrotti, Maria Luiza; Audrain, Samuel; Bin, Nicolas; Boss, Emmanuel; Bowler, Chris; Cassar, Nicolas; Caudan, Loic; Chabot, Genevieve; Cohen, Natalie R.; et al. (Frontiers in Marine Science, 2019)
Interactions between the ocean and the atmosphere occur at the air-sea interface through the transfer of momentum, heat, gases and particulate matter and through the impact of the upper-ocean biology on the composition and radiative properties of this boundary layer. The Tara Pacific expedition, launched in May 2016 aboard the schooner Tara, was a 29-month exploration with the dual goals to study the ecology of coral systems along ecological gradients in the Pacific Ocean and to assess inter-island and open ocean surface plankton and neuston community structures. In addition, key atmospheric properties were measured to study links between the two boundary layer properties. A major challenge for the open ocean sampling was the lack of ship-time available for work at “stations”. This required development of underway sampling approaches to optimize physical, chemical, optical and genomic methods to capture the entire community structure of the surface layers, from viruses 81 through metazoans in their oceanographic and atmospheric physicochemical context. An international scientific consortium was put together to analyze the samples, generate data, and develop datasets in coherence with the existing Tara Oceans database. Beyond adapting the extensive Tara Oceans sampling protocols for high-resolution underway sampling, the key novelties compared to Tara Oceans’ global assessment of plankton include the measurement of (i) surface plankton and neuston biogeography and functional diversity; (ii) bioactive trace metals distribution at the ocean surface and metal-dependent ecosystem structures; (iii) marine aerosols, including biological entities, (iv) geography, nature and colonization of microplastic, and (iv) high-resolution underway assessment of net community production via equilibrator inlet mass spectrometry. We are committed to sharing the data collected during this expedition, making it an important resource to address a variety of scientific questions.nnkton-taxonomy/assemblage/genomics